Modification of a standard protocol for DNA extraction from smaller sandflies (Phlebotominae: Lutzomyia) - GOLCZER, GABRIEL; ARRIVILLAGA, JAZZMÍN (Revista Colombiana de Entomología, 2008)
We evaluated the yield of a potassium acetate protocol with minor modifications for the extraction of genomic DNA. The results showed that using the modified protocol gave a higher DNA yield (0.61, and concentration 37.34 ng/µL) was obtained with respect to the original protocol. The amplification of DNA by PCR for mitochondrial regions demonstrated the high quality of this DNA for molecular population studies, in less time and cost, without the use of highly toxic reagents.